2014
DOI: 10.1111/pbi.12243
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock‐to‐scion transfer of transgene‐derived small interfering RNAs and their effect on virus resistance in nontransgenic sweet cherry

Abstract: SummarySmall interfering RNAs (siRNAs) are silencing signals in plants. Virus-resistant transgenic rootstocks developed through siRNA-mediated gene silencing may enhance virus resistance of nontransgenic scions via siRNAs transported from the transgenic rootstocks. However, convincing evidence of rootstock-to-scion movement of siRNAs of exogenous genes in woody plants is still lacking. To determine whether exogenous siRNAs can be transferred, nontransgenic sweet cherry (scions) was grafted on transgenic cherry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 35 publications
5
74
1
Order By: Relevance
“…5 and 6). The number of mobile t-siRNAs was larger than that shown by Molnar et al [26] in Arabidopsis plants (moving from shoot to root) and from a transgenic sweet cherry root to scion [24]. The size distribution and the profile of the mobile t-siRNA in our experiment was similar to that characterized in the transgenic rootstock, dominated by the 21-to 22-nt sizes, as shown previously in tobacco [29].…”
Section: Size and Distribution Of T-sirna In Transgenic Rootstock Andsupporting
confidence: 84%
See 1 more Smart Citation
“…5 and 6). The number of mobile t-siRNAs was larger than that shown by Molnar et al [26] in Arabidopsis plants (moving from shoot to root) and from a transgenic sweet cherry root to scion [24]. The size distribution and the profile of the mobile t-siRNA in our experiment was similar to that characterized in the transgenic rootstock, dominated by the 21-to 22-nt sizes, as shown previously in tobacco [29].…”
Section: Size and Distribution Of T-sirna In Transgenic Rootstock Andsupporting
confidence: 84%
“…This was in turn processed to siRNA molecules of about 21-24 nt length that directed the RNA silencing pathway [22]. It has been shown that siRNAs produced from hairpin loci can move through the vasculature or a graft union [23,24] and are functional in mediating post-transcriptional gene silencing of endogenous and exogenous targets, [25][26][27]. This trait was exploited for the development of viral resistance of a non-transgenic scion grafted onto transgenic rootstock expressing siRNA to target an invading virus [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, post-transcriptional silencing of an endogenous gene in the shoot was observed in Nicotiana when a wild-type scion was grafted on a rootstock synthesizing a siRNA signal (Kasai et al, 2011). The signal can spread from a rootstock can travel quite far as demonstrated in cherry, where siRNAs were detected 1.2 m from the graft union (Zhao and Song, 2014).…”
Section: Root-to-shootmentioning
confidence: 99%
“…The success of this approach, however, has largely depended on the species, the level of expression and the interactions of the small interfering ribonucleic acid (siRNA) with the target gene [15]. For example, the transfer of transgene-derived siRNAs from the transgenic cherry rootstocks to the non-transgenic scions in grafted trees was effective in inducing resistance to the Prunus necrotic ringspot virus [16]. In apples, however, the transmission of siRNAs from transgenic rootstock to non-transgenic scion was not observed [17].…”
Section: Introductionmentioning
confidence: 99%